2016
DOI: 10.1136/bmjopen-2015-009000
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative process evaluation of training for non-physician clinicians/associate clinicians (NPCs/ACs) in emergency maternal, neonatal care and clinical leadership, impact on clinical services improvements in rural Tanzania: the ETATMBA project

Abstract: ObjectivesThe Enhancing Human Resources and Use of Appropriate Training for Maternal and Perinatal Survival in sub-Saharan Africa (ETATMBA) project is training non-physician clinicians as advanced clinical leaders in emergency maternal and newborn care in Tanzania and Malawi. The main aims of this process evaluation were to explore the implementation of the programme of training in Tanzania, how it was received, how or if the training has been implemented into practice and the challenges faced along the way.De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 14 publications
(14 reference statements)
5
13
0
Order By: Relevance
“…The challenges associated with infrastructure and existence of multiple trainees and thus limited opportunities for practical training as unveiled by this study bring another dilemma in the AMOs training in Tanzania. Although not explicitly the same as what our study has documented, studies from different places in Sub-Saharan Africa reveal inadequacies in the training of the associate clinicians (8,(29)(30)(31)(32). Limited teaching materials as revealed in this study, bring in the challenge of quality of graduates.…”
Section: Discussionsupporting
confidence: 51%
“…The challenges associated with infrastructure and existence of multiple trainees and thus limited opportunities for practical training as unveiled by this study bring another dilemma in the AMOs training in Tanzania. Although not explicitly the same as what our study has documented, studies from different places in Sub-Saharan Africa reveal inadequacies in the training of the associate clinicians (8,(29)(30)(31)(32). Limited teaching materials as revealed in this study, bring in the challenge of quality of graduates.…”
Section: Discussionsupporting
confidence: 51%
“…24 Sadly, in this larger current study, we cannot be certain of this conclusion although our qualitative findings provide some corroboration to our positive findings. 20 It is acknowledged that maternal mortality is still a significant problem, particularly in rural Tanzania. 25 Nelissen et al 25 suggest that there is a great need for the upscaling and use of evidence-based interventions that could help to save lives.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a qualitative study was undertaken time with the trainees and other stakeholders, but this will be reported elsewhere. 20 …”
Section: The Etatmba Project In Tanzaniamentioning
confidence: 99%
“…Earlier studies have reported barriers to accessing Csections as inadequate skilled human resources (medical doctors, gynaecologists, obstetricians, anaesthetists and midwives), 9,10,11 equipment, 12,13,14 commodities, 15 infrastructure, 11,16 delays in accessing services and failure to follow policies and guidelines on quality of C-section care. 13 Tanzania, with an estimated population of 58.4 million, 17 is one of the top 10 countries that contribute to 58% of the global maternal mortality.…”
Section: Essential Supplies Including Blood and Medicinesmentioning
confidence: 99%
“…However, frequent shortages of necessary equipment and consumables were reported in several studies in Tanzania. 16,42,57,58,59 In situations of severe resource constraints where health facilities are provided with far less equipment and drugs than required, health workers find that they are not able to provide the services expected. 60 Stock-outs of life-saving drugs, blood and resuscitation equipment, known to be critical in serving lives in obstetric emergencies, should be a cause of great concern.…”
Section: Equipment and Essential Suppliesmentioning
confidence: 99%